STUDENTS’ PERCEPTION OF POLITENESS IN COMMUNICATING WITH TEACHERS THROUGH INSTANT MESSAGING APPLICATION:A NARRATIVE INQUIRY - Mularsih, Evi Riski; Maudy, Ainurvely G (University of Surakarta, 2020)
This paper aims to determine students' perceptions about etiquette and politeness that must be considered by students when communicating with teachers in an instant messaging application. This study is a qualitative study with a narrative inquiry. The object of research was 8th grade students of Al-Abidin Islamic Middle School Surakarta. The data were collected by interviewing five students from the 8th grade of Al-Abidin Islamic Middle School Surakarta. The results showed that most students already understood the concept of politeness, although it was still simple. Students also understood the reasons why they have to be polite in sending messages to the teachers, although the reasons were more due to age differences. In assessing the contents and the procedures how the way theysend massage, the students have already known which one polite or not.